Heavy metal availability (zinc and copper) in peat soil under oil palm plantation / Haslinda Muhamad Shabri - Muhamad Shabri, Haslinda (Faculty of Plantation and Agrotechnology, 2016)
Heavy metals are non-biodegradable and can remain almost indefinitely in the soil environment. The contamination by heavy metals in soil is one of the important issues and requires attention because heavy metal above the standard of heavy metal limit in soil will threatened to both plants and living things. A study regarding heavy metal availability in peat soil under oil palm plantation and the relationship between concentrations of heavy metal content with different planting ages that affect the availability of heavy metal content at Felcra Sri Mendapat. The soil was collected at different planting ages less than 10, more than 15, and more than 20 years. Simple random sampling was used with three replication of treatments for every week within three week for analysis. One parameter (planting ages) and emphasized on two elements of heavy metal (Zn and Cu). Heavy metals present in soil were determined using the Mehlich 1 method. The result indicates that the heavy metal availability between Zn and Cu in peat soil under oil palm plantation is significant. Results showed that concentration of zinc below standard of heavy metal limit in soil and copper exceed standard of heavy metal limit in soil. The relationship between the concentration of Zn different planting ages is significant except for Cu there is no correlation with the planting ages.